Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12909-021-02507-z
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical foundations of cybercivility in health professions education: a scoping review

Abstract: Background Teaching cybercivility requires thoughtful attention to curriculum development and content delivery. Theories, models, and conceptual and theoretical frameworks (hereafter “tools”) provide useful foundations for integrating new knowledge and skills into existing professional practice and education. We conducted this scoping review to identify tools used for teaching cybercivility in health professions education. Methods Using Arksey and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…However, the findings from the research on AD and TA have not shown conclusive results. In addition, they discussed more about AD issues and proposed possible solutions to address the problem (Adzima, 2020; De Gagne et al, 2021). Meanwhile, the solutions to increase TA in online assessment have not been widely reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the findings from the research on AD and TA have not shown conclusive results. In addition, they discussed more about AD issues and proposed possible solutions to address the problem (Adzima, 2020; De Gagne et al, 2021). Meanwhile, the solutions to increase TA in online assessment have not been widely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, TA is an effort to avoid the emergence of AD from students. Given the limited comprehensive systematic review of AD and TA in the context of online assessment, most current studies focus on addressing AD problems, and issues about developing strategies to increase TA are not widely reported (e.g., Adzima, 2020; De Gagne et al, 2021). In this study, the comprehensive results from related studies in the last 5 years are expected to contribute to educators and researchers to minimize AD behaviour and improve TA practices in online assessments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a recent estimate, social media is becoming increasingly popular globally; more than 2.65 billion people were SM users, whereas this figure is expected to reach 3 billion by 2021 [ 10 ]. Such rapid growth in SM users indicates that SM has vast potential for knowledge sharing and networking [ 11 ]. SM use in health sciences is also extensive; customers of the health sector may use it to get better information about health services, get reviews on some therapeutic methods, or share their personal experiences about a health service [ 12 ].…”
Section: Introductionmentioning
confidence: 99%